Safety, tolerability, pharmacokinetics, and immunogenicity of an anti-SARS-CoV-2 monoclonal antibody HFB30132A after single dose intravenous administration in healthy Chinese subjects: a phase 1, randomized, double-blind, placebo-controlled study - Li, Shanshan; Wu, Xiaojie; Li, Nanyang; Cao, Guoying; Wang, Jingjing; Chen, Yuancheng; Li, Size; He, Jinjie; Wu, Jufang; Yang, Haijing; Lin, Ke; Qiu, Chao; et al. (Frontiers in Pharmacology, 2023)
Objective: The pandemic of coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) still protracts worldwide. HFB30132A is an anti- SARS-CoV-2 monoclonal antibody purposely engineered for an extended half-life with neutralizing activity against majority of the virus variants identified so far. The aim of this study was to evaluate the safety, tolerability, pharmacokinetics (PK), and immunogenicity of HFB30132A in healthy Chinese subjects. Methods: A phase 1, randomized, double-blind, placebo-controlled, single ascending dose clinical trial was designed. Twenty subjects were enrolled to Cohort 1 (1000 mg dose level, 10 subjects) or Cohort 2 (2000 mg dose level, 10 subjects). Subjects in each cohort were assigned randomly to receive a single intravenous (IV) dose of HFB30132A or placebo at a ratio of 8:2. Safety was assessed in terms of treatment emergent adverse events (TEAEs), vital signs, physical examination, and ECG findings. PK parameters were measured and calculated appropriately. Anti-drug antibody (ADA) test was performed to detect anti-HFB30132A antibodies. This study is registered at ClinicalTrials.gov (identifier: NCT05275660). Results: All subjects completed the study. Overall, 13 (65%) of the 20 subjects experienced TEAEs. The most common TEAEs were laboratory abnormalities (12 subjects [60%]), gastrointestinal disorders (6 subjects [30%]), and dizziness (4 subjects [20%]). All TEAEs were Grade 1 or Grade 2 in severity according to the criteria of Common Terminology Criteria for Adverse Events (CTCAE). Serum exposure (Cmax, AUC0-t, AUC0-∞) of HFB30132A increased with ascending dose. After single dose of 1000 mg and 2000 mg HFB30132A, the mean Cmax was 570.18 μg/mL and 898.65 μg/mL, the mean AUC0-t value was 644749.42 h*μg/mL and 1046209.06 h*μg/mL, and the mean AUC0-∞ value was 806127.47 h*μg/mL and 1299190.74 h*μg/mL, respectively. HFB30132A showed low clearance ranging from 1.38 to 1.59 mL/h, and a long terminal elimination half-life (t½) of 89-107 days. ADA test did not detect any anti-HFB30132A antibodies. Conclusion: HFB30132A was safe and generally well-tolerated after single IV dose of 1000 mg or 2000 mg in healthy Chinese adults. HFB30132A did not induce immunogenic response in this study. Our data support further clinical development of HFB30132A.